Handbuch Hochschulbibliothekssysteme: Leistungsfähige Informationsinfrastrukturen für Wissenschaft und Studium - Söllner, Konstanze (De Gruyter Saur, 2014)
Changing conditions are forcing university libraries to redesign how academic information is supplied to users. The Handbook of University Library Systems presents planning recommendations from the German Council of Science and Humanities and the German Research Foundation, and explores a number of delivery models using examples taken from professional practice
Keywords: Aufsatzsammlung; Informationsversorgung; Hochschulbibliothek; Bibliothekssystem; Infrastrukturplanung